Dampak Consumer-Based Brand Equity pada Consumer Attitude dan Consumer Intention terhadap Electronic Word Of Mouth (E-WOM) pada Brand Somethinc - Muhammad Ramadheo Nugraha; Heppy Millanyani; Eva Nurhazizah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to ascertain how Consumer-Based Brand Equity affects Consumer Attitudes and intentions when it comes to electronic word-of-mouth (e-WOM) for the Somethinc brand. The Consumer-Based Brand Equity hypothesis is used in this study to evaluate a model that illustrates how Consumer Attitude, intention, and e-WOM for the Somethinc brand are influenced by Consumer-Based Brand Equity.This study uses a cross-sectional approach and is quantitative in nature. Indonesian customers of Certain brands make up the population. Purposive sampling was used to determine the sample size, and 150 respondents met the criterion of being current Somethinc brand consumers. Using the SmartPLS 3.0 software, structural equation modeling, or SEM, is the data analysis method employed.The study's findings show that: (1) Consumer Attitude Toward the Somethinc brand is positively and significantly impacted by Brand Image . (2) Consumer Attitudes toward the Somethinc brand are positively and significantly impacted by brand awareness. (3) Consumer Intention to participate in e-WOM for the Somethinc brand is positively and significantly impacted by Brand Image . (4) Consumer Intention to participate in electronic word-of-mouth (e-WOM) for the Somethinc brand is positively correlated with brand awareness.The study's findings and suggestions indicate that the Somethinc brand needs to strengthen and enhance its Brand Image in the eyes of consumers through strategies such as broader advertising campaigns, a strong presence on social media, and active consumer engagement. Future research is recommended to test the model on other brands and compare the results, as well as to examine other factors that may influence e-WOM.